2017
DOI: 10.1097/adm.0000000000000299
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women's Current and Intended Cannabis Use in Relation to Their Views Toward Legalization and Knowledge of Potential Harm

Abstract: Cannabis use during pregnancy is relatively common and persistent, despite knowledge of the potential risks of harm. Views toward legalization vary among pregnant women and may impact cannabis use during pregnancy. In a changing legal climate, there is a need for clear messaging on the effects of cannabis use during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
149
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(154 citation statements)
references
References 26 publications
3
149
1
1
Order By: Relevance
“…In a nationally representative sample of pregnant women, the proportion of individuals perceiving no risk of harm from regular cannabis use increased substantially among both cannabis users (25.8% to 65.4%) and nonusers (3.5% to 16.5%) between 2005 and 2015 . In another study, 10% of pregnant women indicated that they would use cannabis more during pregnancy if it were legalised . Of concern, this practice may also be endorsed by cannabis retailers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a nationally representative sample of pregnant women, the proportion of individuals perceiving no risk of harm from regular cannabis use increased substantially among both cannabis users (25.8% to 65.4%) and nonusers (3.5% to 16.5%) between 2005 and 2015 . In another study, 10% of pregnant women indicated that they would use cannabis more during pregnancy if it were legalised . Of concern, this practice may also be endorsed by cannabis retailers.…”
Section: Discussionmentioning
confidence: 97%
“…This observation aligns with the hypothesis that women may discontinue their cannabis use once they become aware of the pregnancy or that they may turn to cannabis to alleviate nausea and vomiting during the first trimester. Accordingly, a small survey of pregnant women revealed that almost all women who continued to use cannabis after pregnancy diagnosis did so to self‐treat symptoms of morning sickness . Furthermore, in a sample of over 200 000 pregnant women, those with severe (aOR = 3.80, 95% CI 3.19–4.52) or mild (aOR = 2.37, 95% CI 2.17–2.59) nausea or vomiting of pregnancy had increased odds of cannabis use in the first trimester relative to women without these symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a survey of women in Vancouver, Canada found that up to 77% of medicinal cannabis use during pregnancy was related to nausea; over 50% of respondents also reported cannabis use to treat a lack of appetite, general pain, insomnia, anxiety, depression and fatigue (Westfall et al, 2009). Despite knowledge of potential fetal health risks, cannabis use in pregnant women is becoming more commonplace and the need for clear messaging on the safety of use during pregnancy is urgently needed (Mark et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…It is also the most commonly used illicit drug used among pregnant women 2 in the United States, with prevalence rates ranging from 3-4% 3 and higher rates among pregnant adolescents 4 . Given the recent legalization of cannabis in many states, the perception that cannabis is safe to consume during pregnancy 5 , and the reported intention of use among pregnant women despite knowledge of potential risks 6 , the availability and use of cannabis among pregnant women is likely to increase. Importantly, maternal ingestion of Δ9-tetrahydrocannabinol (THC), the primary psychoactive constituent in cannabis, can have direct effects on fetal development, as THC and its metabolites can freely pass across the placenta 7 .…”
Section: Introductionmentioning
confidence: 99%